Toll-Like Receptor 4 Inhibits Estradiol Secretion via NF-κB Signaling in Human Granulosa Cells - Guan, Hai-Yun; Xia, He-Xia; Chen, Xiu-Ying; Wang, Lu; Tang, Zhi-Jing; Zhang, Wei (Frontiers in Endocrinology, 2021)
Toll-like receptor 4 (TLR4) may play a critical role in regulating follicular development. Data are scarce on the role of TLR4 in the follicle. This study investigated the effects of TLR4 on steroidogenesis in human granulosa cells. Immunohistochemical analysis revealed stage-specific expression of TLR4 in the mouse ovarian cycle, and immunofluorescence showed TLR4 expression in the human granulosa-like tumor cell line (KGN). TLR4 agonist lipopolysaccharides (LPS) significantly inhibited follicular development and synthesis of estradiol (E2) in mice. In KGN cells, TLR4 activation significantly inhibited CYP19A1, FSHR and StAR, and TLR4 inhibition reversed these effects. TLR4 activation also inhibited forskolin-induced secretion of E2 by inhibiting CYP19A1, with no effect on progesterone. Further studies showed activation of p38, JNK and NF-κB signaling after TLR4 activation. Subsequent analyses showed that an NF-κB antagonist reversed the inhibitory effects on CYP19A1 expression and E2 secretion. Together, our results suggest that TLR4 activation may suppress CYP19A1 expression and E2 secretion via NF-κB signaling in human granulosa cells, with important implications for the regulation of ovarian pathophysiology.